Food and feeding habits of Johnieops sina (Cuvier, 1830) along Cochin coast of India - Venugopal, N.; Pillai, N. G. K.; Prakasan, D. (Indian Journal of Fisheries, 2014)
Food and feeding habits of Johnieops sina were studied along the Cochin coast during the period 2008-2010. Johnieops sina mainly feed on crustaceans followed by teleost fishes and the juveniles mainly feed on Acetes. Highest percentage of penaeid prawns and fishes was observed in 190-199 mm and 160-169 mm length groups, respectively. Incidence of empty stomach was high in all months. Intense feeding in male fishes was observed during April, September, October and November, whereas the females fed intensively during December and January